Students’ Perception Toward the Implementation of Project-based Learning in English Speaking Class of English Department Students Academic Year 2024 at UNP - Hasibuan, Marisa Destia; Ramadhani, Syafitri (Journal of English Language Teaching, 2025)
This research investigates students' perceptions toward the implementation of Project-Based Learning (PjBL) in English speaking classes among the English Department students at Universitas Negeri Padang in the academic year 2024/2025. The background arises from the need to address the challenges in speaking skills, such as low confidence, fear of making mistakes, and limited vocabulary, and how PjBL may help mitigate these issues through real-world task engagement. The study used a descriptive quantitative method with a questionnaire distributed to 26 students. The instrument was based on three perceptual factors by Robbins & Judge (2013): perceiver, target, and situation, covering 12 elements. The findings reveal that students hold a very positive perception of the implementation of PjBL. The majority agreed that PjBL improved motivation, collaboration, engagement, and speaking fluency. Students also appreciated the practical value of PjBL in developing their communication, group interaction, and confidence. These results support the effectiveness of PjBL as a student-centered strategy in English speaking class.This research investigates students' perceptions toward the implementation of Project-Based Learning (PjBL) in English speaking classes among the English Department students at Universitas Negeri Padang in the academic year 2024/2025. The background arises from the need to address the challenges in speaking skills, such as low confidence, fear of making mistakes, and limited vocabulary, and how PjBL may help mitigate these issues through real-world task engagement. The study used a descriptive quantitative method with a questionnaire distributed to 26 students. The instrument was based on three perceptual factors by Robbins & Judge (2013): perceiver, target, and situation, covering 12 elements. The findings reveal that students hold a very positive perception of the implementation of PjBL. The majority agreed that PjBL improved motivation, collaboration, engagement, and speaking fluency. Students also appreciated the practical value of PjBL in developing their communication, group interaction, and confidence. These results support the effectiveness of PjBL as a student-centered strategy in English speaking class.